A comparative study on role of phase change materials in thermal efficiency enhancement of passive solar still. (2020) - Naveenkumar, R.; Nandha Gopan, S.; Karthikeyan, N.; Santhosh Kumar, PC.; Ravichandran, M.
Abstract: Solar still is a feasible technical process to change the saline water in to drinking water economically. The main problem in solar still is the thermal energy dissipation from walls of the SS basin and consequently it reduces the performance of the solar desalination system. A PCM will be a suitable remedy and it absorbs heat during day time and can be utilized during non availability of solar radiation. This article explains the technique of utilizing PCM in SS and productivity enhancement of still due to utilization of phase change material. Different PCM's in SS are investigated in this review and the results reveals that the paraffin wax PCM posses maximum output amongst palmitic acid, myristic acid, lauric acid, capric acid, bees wax, bitumen, capric acid and stearic acid. The utilization of paraffin wax enhances the exergy efficiency, energy efficiency and productivity of a passive SS by 40%, 67% and 180%. Incorporation of paraffin wax in the void circular pin fins has emerged as efficient method to enhance the thermal conductivity (K) value. This method enhances energy efficiency and yield of SS by 37.50% and 12%.